"Eurowhite" Conceit, "Dirty White" Ressentment: "Race" in Europe. Issue 4 (13th October 2021) - Böröcz, József
Abstract : This paper offers tools to rethink global critical insights on "race" in the contemporary structural transformation of European identity politics from the perspectives of postcolonial global historical sociologies. "Race" regimes rest on the following background assumptions: (1) The claim that humankind consists of a finite number of disjunct (non‐overlapping) "groups, " "populations" or, in the extreme, "races"; (2) The presumption that it is valid to arrange those "groups, " "populations" or "races" in a system of moral super‐ and subordination; (3) The contention that the resulting moral hierarchy forms a single constant, irrespective of socio‐historical contexts, criteria, or purposes of comparison; (4) Insistence that single, ahistorical/decontextualized hierarchy can be mapped on to body shape, skin pigmentation or other epiphenomenal "features" of "groups, " "populations, " or "races, " such that (5) "Whiteness" is always already at the top, "Blackness" is always already at the bottom of that hierarchy. This paper focuses on the workings of "Whiteness" as a moral‐geopolitical superiority claim, whose defining element is an ahistorical/decontextualized claim, indeed demand, for unconditional global privilege. "Whiteness" is an unfounded, un‐found‐able—hence eminently unstable and contested—identity category. It is a relational category whose core is fixed as a constant, inaugurating the "White" subject's relations ("superiority") to its constitutive outside. I introduce two conceptual innovations: "eurowhiteness"—result of an internal structuring of the category of "Whiteness" whose purpose is separating an even more exalted, even more superior "cultural" —"racial" distinction within the universe of "Whiteness" and "dirty whiteness"—to capture the epistemic position of quantitative undervalued, positions within the moral quasi‐community of "White" claims for global privilege, especially in their east European variants.